Supporting Refugees in Rural Canada: Exploring the Strengths and Weaknesses of Settlement Service Models in Smaller Communities - Haugen, Stacey; McNally, Rachel; Hallstrom, Lars (Refuge, 2025)
This article demonstrates how refugee integration is supported in rural and small communities across Canada. We conducted virtual focus groups and interviews with 40 participants across the country who support refugees through settlement organizations, sponsorship groups, and other networks. The article outlines six participant-identified models of settlement services and explores the benefits, challenges, and limitations of and potential improvements for each model. These models highlight the mix of formal and informal supports existing in rural places and the urban focus of Canada’s settlement system. Recommendations include adequate funding of settlement services in smaller communities and engaging with rural service providers.